(untitled) (Current Horticulture, 2024)
A field experiment was conducted at the Regional Research Station (Hill Zone), Uttar Banga Krishi Viswavidyalaya, Kalimpong, Darjeeling, West Bengal, during 2019 and 2020 to study the effect of weed diversity, growth and yield of ginger (Zingiber officinale Rose) as influenced by organic mulching and alternative weed management practices. The randomized block design, having seven varying treatments with three replications was used. The treatments consisted of dry weed biomass mulch @ 5.0 t/ha (T1), paddy straw mulch @ 5.0 t/ha (T2), FYM Mulch @ 5.0 t/ha (T3), dry leaves of Schima wallichi@ 5.0 t/ha (T4), dry leaves of Artimesia sp. and Eupatorium sp. @ 5.0 t/ha (T5), hand weeding (twice) at 45 and 90 DAS (T6) and unweeded control (T7). The result showed that hand weeding twice at 45 and 90 DAS (T6) appreciably reduced the total weed population/m2 and total dry weight of weeds than unweeded control plot (T7) at all the stages of crop growth. The highest plant height (82.10 cm), number of leaves/clump (65.41), number of pseudo stem/clump (5.17), rhizome length (7.22 cm), rhizome width (5.50 cm), number of fingers/rhizome (6.42), yield/plant (0.268 kg/plant), yield (20.33 t/ha) and weed control efficiency were recorded under the hand weeding twice at 45 and 90 DAS (T6) compared to other treatments. The results showed that it is necessary to cover the soil surface with different mulch materials and manual weed control practices to achieve a good control of weeds along with enhanced yield attributes and yield.